Transaortic Transcatheter Aortic Valve Implantation and Concomitant Off Pump Revascularization. Issue 5 (September 2016) - Baumbach, Hardy; Ahad, Samir; Hill, Stephan; Schäufele, Tim; Adili, Sara; Wachter, Kristina; Franke, Ulrich F. W.
Abstract : Abstract: An increasing number of patients with severe aortic stenosis and concomitant critical coronary artery disease were referred to our hospital. Some of those patients were classified as high-risk patients qualifying for a transcatheter therapy with the additional need for coronary revascularization. As a consequence of their comorbidities, the established transapical as well as transfemoral approach were either not possible or not favored owing to the indispensable need for coronary revascularization. We present 4 successfully combined off-pump procedures consisting of a transcatheter aortic valve implantation (Edwards SAPIEN XT) via the transaortic approach and an off-pump coronary artery bypass grafting. All patients were discharged free from stroke, myocardial infarction, or access site complications either to rehabilitation facility or to the referring hospital with none or trace aortic regurgitation and patent grafts. These cases confirm the feasibility of those combined operations and should be considered as realistic alternative for surgical treatment in high-risk patients who are clearly identified to benefit from transcatheter approach to treat aortic stenosis and who have severe concomitant coronary artery disease.